Correlation Between Gratitude and Social Comparison with Body Image in Vocational High School (SMK) Students - Della Tri Damayamti; Ahmad Saifuddin (Universitas Islam Tribakti Lirboyo Kediri, 2022)
This study aimed to determine the correlation between gratitude and social comparison with body image in adolescents. This research used a quantitative approach with the correlation study involving 136 students of the Online Marketing and Business Expertise Program at SMK Negeri 3 Surakarta, female students aged 15-18 years. Data were collected using a measuring instrument for gratitude using the concept of Al Ghazali, a measuring instrument for social comparison using the theory of Jones, and a measuring instrument for body image using the theory of Cash & Pruzinsky. This study used content validity by involving seven experts or raters. The results showed that gratitude had a reliability coefficient of 0.917, the social comparison had a reliability coefficient of 0.913, and body image had a reliability coefficient of 0.883. Based on hypothesis testing using multiple regression analysis, the results showed that gratitude and social comparison simultaneously had a significant correlation with body image, with a correlation coefficient of 0.192 and a significance value of 0.000 (p <0.05). Then partially, gratitude had a positive correlation with body image, with a correlation coefficient of 0.425 with a significance value of 0.001 (p <0.05). Meanwhile, the social comparison had no correlation with body image because it had a correlation coefficient of -0.342 with a significance value of 0.178 (p>0.05).